Application of Ge Nanowire for Two-Input Bistable Nanoelectromechanical Switch - Jana ANDZANE; Juris PRIKULIS; Raimonds MEIJA; Jelena KOSMACA; Subhajit BISWAS; Justin D HOLMES; Donats ERTS (Medžiagotyra, 2013)
Recently, several research groups presented bistable two-terminal nanoelectromechanical switches based on individual single-clamped active element. All presented devices had one input electrode. Similar devices having two or more input electrodes have not been yet investigated. In this work we present the two-input bistable controlled nanoelectromechanical switch based on an individual single-clamped Ge nanowire. The switch is realised using in-situ SEM technique and operating due to balancing of electrostatic, adhesion and elastic forces. The operation conditions of the device are investigated and presented. The advantages and drawbacks of the device are discussed. DOI: http://dx.doi.org/10.5755/j01.ms.19.3.3086